Research issues in biological inspired sensors for flying robots - Silva, Manuel (2019)
Biological inspired robotics is an area experiencing an increasing research and development. In spite of all the recent engineering advances, robots still lack capabilities with respect to agility, adaptability, intelligent sensing, fault-tolerance, stealth, and utilization of in-situ resources for power when compared to biological organisms. The general premise of bio-inspired engineering is to distill the principles incorporated in successful, nature-tested mechanisms of selected features and functional behaviors that can be captured through biomechatronic designs and minimalist operation principles from nature success strategies. Based on these concepts, robotics researchers are interested in gaining an understanding of the sensory aspects that would be required to mimic nature design with engineering solutions. In this paper are analysed developments in this area and the research aspects that have to be further studied are discussed.